2015
DOI: 10.1038/nature15758
|View full text |Cite
|
Sign up to set email alerts
|

Migratory neuronal progenitors arise from the neural plate borders in tunicates

Abstract: The neural crest is an evolutionary novelty that fostered the emergence of vertebrate anatomical innovations such as the cranium and jaws1. During embryonic development, multipotent neural crest cells are specified at the lateral borders of the neural plate before delaminating, migrating, and differentiating into various cell types. In invertebrate chordates (cephalochordates and tunicates), neural plate border cells express conserved factors such as Msx, Snail, and Pax3/7 and generate melanin-containing pigme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
200
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(209 citation statements)
references
References 50 publications
9
200
0
Order By: Relevance
“…We are also curious about the final fate of A10.64 derivatives, which migrate anteriorly along the neural tube as the tail extends. It is conceivable that these cells respond to the same migratory cues as the BTN cells, which possess some of the properties of neural crest derivatives (Stolfi et al, 2015). It is also possible that A10.64 cells correspond to Islet-positive neurons of the visceral ganglion (Stolfi and Levine, 2011) rather than A10.57.…”
Section: Revised Lineage Of A-line Neural Cellsmentioning
confidence: 99%
“…We are also curious about the final fate of A10.64 derivatives, which migrate anteriorly along the neural tube as the tail extends. It is conceivable that these cells respond to the same migratory cues as the BTN cells, which possess some of the properties of neural crest derivatives (Stolfi et al, 2015). It is also possible that A10.64 cells correspond to Islet-positive neurons of the visceral ganglion (Stolfi and Levine, 2011) rather than A10.57.…”
Section: Revised Lineage Of A-line Neural Cellsmentioning
confidence: 99%
“…Another example of more lateral Msx/ vab-15 expression exists in the urochordate C. intestinalis. Two NPB cells (b8.18 and b8.21) give rise to BTNs, which are likely the counterparts to vertebrate dorsal root ganglion (DRG) mechanosensory neurons (9) (Fig. 4C).…”
Section: The Npb Specification Module Is Conserved Between Worm Andmentioning
confidence: 99%
“…The laterally located V5 and Q neuroblasts give rise to PNS neurons; that is, V5 neuroblasts give rise to the mechanosensory neuron PVD, whereas QL and QR neuroblasts give rise to the migratory mechanosensory neurons AVM and PVM, respectively (10). Furthermore, Q neuroblasts undergo delamination and migrate along prototypical paths while dividing and differentiating (10), similar to the neural crest in vertebrates and mechanosensory bipolar tail neurons (BTNs) in tunicate (3,9). At the molecular level, Msx/vab-15 establishes the identity of the lateral boundary of the neuroectoderm in fly, annelids, amphioxus, lamprey, and higher vertebrates.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bill Jeffery identified migratory pigment cells in ascidians (Jeffery et al 2004;Jeffery 2006) and, more recently, Lionel Christiaen's group identified migrating neuron precursors in the ascidian Ciona intestinalis. Interestingly, these precursors were shown to arise from the border of the neural plate, a hallmark of the neural crest in vertebrates (Stolfi et al 2015).…”
Section: A Short Natural History Of the Nervous System: Several Questmentioning
confidence: 99%